Adaptive and Personalized Web Blog Searching Technique Using S-ANFIS. (27th August 2022) - Khatter, Harsh; Malik, Pooja; Jyoti, Amrita; Ahlawat, Anil Kumar; Dubey, Gaurav; Mishra, Anurag; Neupane, Sanjeev Chandra
Abstract : Day by day, the number of blog users and microblog users is increasing worldwide. It is easy to say that blogs have captured a significant portion of other web services. In the past few years, the number of users has exponentially increased. User count of Facebook, Twitter, and Instagram applications is not hidden from anyone. Users on such platforms share ideas, experiences, stories, opinions, and views and want to interact with people with the same set of interests. As per the user's expectation, there is a requirement of two things: content curation and recommendations . The content curation algorithm will find the people and their posts on personalized search results. In addition, the recommendation system will help to find the most appropriate match to interact with. In this paper, both approaches are combined to show the user's curated and recommended results. The article focuses on the hybrid model named S-ANFIS, and the results are compared with the well-known approaches like ANN, Deep Neural Network (DNN), and Recurrent Neural Network (RNN).